Psychological effects of spinal cord injury :an Exploration into the subjective experiences of spinal cord injured persons at Dr Mukhari Hospital - Tshabalala, B.G. (My University, 2012)
Spinal cord injury (SCI) is believed to place the individual at a high risk of psychological turmoil. This study explored the subjective experiences of SCI persons, by exploring the psychological effects of SCI at Dr. George Mukhari Hospital. To achieve this, the primary objectives of the study were to; explore the psychological effects faced by SCI individuals; and explore the impact of these effects in their lives and well-being. Participants included eight SCI persons who were in the rehabilitation programme. A qualitative exploratory enquiry approach was utilised, by conducting semi-structured interviews. Data was analysed using a thematic analysis. Two main themes emerged: the psychological effects of SCI and impact of these effects on the well-being of the person. The psychological effects faced by SCI persons were linked to diminished independence, intrapersonal changes, altered interpersonal relationships and emotional disturbance. The psychological effects seemed to be devastating to the optimal functioning of the participants. The impact of these effects was perceived as life changing. The impact of the psychological effects of SCI was linked to psychological adjustment. Psychological adjustment referred to the variety coping strategies adopted by participants and their perceptions post injury. The coping strategies included effective and ineffective coping strategies. Most participants struggled as they attempted to make sense of the effect of SCI. Life post- injury was perceived with mixed emotions that of being hopeful and on other hand fearful; hopeful that their (participants) condition would change for the better, yet fearful as to what if it does not. As to deal with the devastating impact of SCI, participants engaged in a process of reconstructing the self, coming to terms with disability, and striving for maintaining a positive outlook post-SCI. v In conclusion, understanding how SCI persons view themselves post-injury is a prerequisite to the development of appropriate SCI psychological strategies to facilitate optimal functioning. Thus psychological adjustment remains critical in determining the rehabilitation process post injury.
Thesis (MSc. (Clinical Psychology)) -- University of Limpopo (Medunsa Campus), 2012
Keywords: Spinal cord injury; Spinal cord